Edukasi Isi Piringku Sebagai Upaya Pencegahan Anemia Pada Ibu Hamil - Tutik Ekasari (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Anemia in pregnancy is a condition where the hemoglobin (Hb) level in the blood is less than normal and the hemoglobin (Hb) level in the mother decreases from the normal Hb level, which is <11 g / dL. Anemia that often occurs in pregnancy is iron deficiency anemia which is referred to as a "potential danger to mother and child" (potential to endanger mother and child). The purpose of this PKM is to increase maternal knowledge in preventing anemia in pregnancy and the output target to be achieved is the Community Service Journal. The method of this Community Service is health education to women of childbearing age about the contents of my plate. Participants in this Community Service are women of childbearing age and cadres, totaling 30 people. The location of the Community Service is in Pajurangan Village, Gending District, Probolinggo Regency. Based on the results of the PKM activity on Saturday, May 31, 2025, participants understand and are able to explain again about the contents of my plate as an effort to prevent anemia, especially for pregnant women. This Community Service is expected to provide understanding and change community behavior. To overcome the problem of anemia, the role of Posyandu cadres is needed to provide information about the importance of understanding the contents of my plate for balanced nutrition.